2021
DOI: 10.3390/s21123965
|View full text |Cite
|
Sign up to set email alerts
|

Smart City Data Sensing during COVID-19: Public Reaction to Accelerating Digital Transformation

Abstract: The article presents the results of the analysis of the adaptation of metropolis IT technologies to solve operational problems in extreme conditions during the COVID-19 pandemic. The material for the study was Russian-language data from social networks, microblogging, blogs, instant messengers, forums, reviews, video hosting services, thematic portals, online media, print media and TV related to the first wave of the COVID-19 pandemic in Russia. The data were collected between 1 March 2020 and 1 June 2020. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Te pooling layer performs feature dimension reduction [21]. Te proposed method uses the max-pooling method to extract the largest feature from the local feature set obtained by the convolution layer to replace the entire local feature 􏽢 f i , and the calculation is as follows:…”
Section: Pooling Layermentioning
confidence: 99%
“…Te pooling layer performs feature dimension reduction [21]. Te proposed method uses the max-pooling method to extract the largest feature from the local feature set obtained by the convolution layer to replace the entire local feature 􏽢 f i , and the calculation is as follows:…”
Section: Pooling Layermentioning
confidence: 99%
“…Data mining technology can also analyze citizens' attitudes towards daily life status or policies. Kharlamov et al (2021) The researchers found that due to the COVID-19 pandemic, there are differences in how well people adapt to IT technology. Digital services in smart cities have received mixed reviews.…”
Section: Smart Iot Data and Smart Service And Applicationmentioning
confidence: 99%
“…Information entropy represents the information gain of uncertainty. It can measure the impact of a feature on the classification results of enterprise transformation effectiveness [15,16]. Information entropy is expressed as follows:…”
Section: Information Gainmentioning
confidence: 99%